2013
DOI: 10.3892/etm.2013.1416
|View full text |Cite
|
Sign up to set email alerts
|

Metformin inhibits proliferation of human keratinocytes through a mechanism associated with activation of the MAPK signaling pathway

Abstract: In the present study, the effects of metformin on the proliferation of human immortalized keratinocytes (HaCaTs) and the underlying mechanisms were investigated. HaCaT cells in the logarithmic growth phase were treated with 50 mM metformin for 24, 48 and 72 h. Cell morphology after 24 h of treatment was observed under a microscope. Cell proliferation was detected using a colorimetric cell proliferation and cytotoxicity assay kit. Western blot analyses were performed to detect the protein phosphorylation levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
27
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 20 publications
3
27
0
1
Order By: Relevance
“…To study the mechanism of metformin in treating epidermal hyperplastic diseases such as psoriasis, we previously reported that metformin inhibited HaCaT cells proliferation in vitro by upregulating AMPK and Erk pathway (Li et al, 2014). In the current study, we found that metformin not only inhibited cell proliferation but also induced HaCaT cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To study the mechanism of metformin in treating epidermal hyperplastic diseases such as psoriasis, we previously reported that metformin inhibited HaCaT cells proliferation in vitro by upregulating AMPK and Erk pathway (Li et al, 2014). In the current study, we found that metformin not only inhibited cell proliferation but also induced HaCaT cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of the mTOR pathway can inhibit multiple proinflammatory cytokines including IL-6, TNF-a, and VEGF (Kirsch et al, 2012), which play important roles in the pathogenesis of psoriasis. Our previous study showed that metformin could inhibit the proliferation of human keratinocytes in association with the activation of the AMPK signaling pathway (Li et al, 2014). However, whether metformin suppresses human keratinocyte proliferation by specifically targeting the mTOR signaling pathway has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the extent of involvement and effect on the quality of life, psoriasis may be mild to moderate in severity. This approach, in turn, forms the basis of treatment in a majority of patients [2].…”
Section: Introductionmentioning
confidence: 99%
“…MF is an anti-diabetic drug which - besides improving glycaemic control - alters multiple pathways in benign and transformed cells leading to the inhibition of proliferation, cell cycle arrest and apoptosis [1,2,3]. …”
Section: Purposementioning
confidence: 99%